Utilization of Digital Marketing on Business WhatsApp Accounts as a Marketing Strategy for MSME Mart Products, Cooperative for Prosperous Citizen Development in Teluk Pucung, Bekasi - Rr Dinar Soelistyowati; Abdul Harits Nurhidayat; Shellin Dwi Aliza (Indonesian Journal of Society Development, 2023)
This research is to produce a Student Centered Learning learning model where this learning method focuses on improving and developing students' critical abilities. So that students get a portion to be more active in the learning process. The learning process also occurs in two directions. Students gain knowledge through studying individually, in groups to explore problems and not become passive recipients of knowledge. Through this learning, it is hoped that we can develop the human resource qualities that society needs, such as creativity, leadership, self-confidence, independence, discipline, critical thinking, communication skills and working in teams, technical expertise and global insight